Factors Related to Giving MPASI in Babies Aged 0-6 Months in the Region Mongeudong Health Center Work Sub-District Banda Sakti Lhokseumawe - Zeva Juwita; Samsidar Sitorus; Rina Hanum (Newinera Publisher, 2020)
There are a number of factors that are thought to be related to the behavior of giving complementary foods such as predisposing factors, supporting factors and driving factors. This study aims to analyze the factors associated with giving complementary foods to infants aged 0-6 months. This type of research is survey research with quantitative and qualitative approaches (Mixed Methods). The research was conducted in the working area of ​​Puskesmas Mongeudong, Banda Sakti District, Lhokseumawe City. Population of 266 people and sample of 160 people. The research informants were 6 people. Quantitative data analysis was univariate, bivariate with the Chi-Square test, and multivariate with multiple logistic regression tests at the 95% confidence level ( = 0.05). The results showed that the factors associated with giving complementary foods to infants aged 0-6 months in the Mongeudong Community Health Center were work (p = 0.016), culture (p = 0.000), infant condition (p = 0.028), and family support (p. = 0.002). Meanwhile, the unrelated factors were education (p = 0.092), knowledge (p = 0.070), maternal condition (p = 0.060), advertising exposure (p = 0.589). The most dominant factor associated with giving complementary foods to infants aged 0-6 months is culture. Mothers who follow culture have the opportunity to provide complementary foods 91.63 times higher than mothers who do not follow the culture. The culture that is still practiced today is peucicap. Another culture is that the mother gives the baby starch water, salt water mixed with sugar (ie sira), scraped bananas, and banana rice at the age of less than 6 months. The habits of the Acehnese people in the care of mothers and babies are usually carried out by their grandmothers who are still healthy.